Surplus: The Politics of Production and the Strategies of Everyday Life 2015
DOI: 10.5876/9781607323808.c004
|View full text |Cite
|
Sign up to set email alerts
|

Surplus in the Indus Civilization: Agricultural Choices, Social Relations, Political Effects

Abstract: FI GUR E S viii 5.2. Småland Plateau 5.3. Cairn areas of early vs. late clearance 5.4. Development of infrastructure in early Jönköping 5.5. Four study blocks with varying proximity to state-building infrastructure 5.6. Example of settlement phases and expansions-Skärstad-Ölmstad Valley 6.1. Land claims and later farm properties in Skagafjörður, northern Iceland 6.2. Chayanov's model defining labor effort to meet household subsistence needs based on the marginal utility and increasing drudgery associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Retaining a local cropping system with regular use of a lower yielding and lower calorific crop may therefore relate not only to environment but may also reflect local identity and choices (e.g. Fuller et al 2004;Fuller 2005;Smith 2006;Miller 2015). Ethnographic work looking at the functionality of all the cereals used (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Retaining a local cropping system with regular use of a lower yielding and lower calorific crop may therefore relate not only to environment but may also reflect local identity and choices (e.g. Fuller et al 2004;Fuller 2005;Smith 2006;Miller 2015). Ethnographic work looking at the functionality of all the cereals used (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…586-587;Luthra 1936), and field pea (Wheeler 1968, pp. 84-85), all of which would have been grown with the support of late summer inundation resulting from Himalayan snow-melt and monsoon rain in the regions to the northeast, complemented by winter rain (see Miller 2006Miller , 2015Petrie 2017). Thinking primarily about the areas of Baluchistan and Sindh, Fairservis (1967Fairservis ( , 1971) subsequently hypothesised that winter or rabi cultivation was the norm for the Indus region.…”
Section: Indus Subsistence and The Issue Of 'Multi-cropping'mentioning
confidence: 99%
“…It is important to note, however, that variation in the distribution of rainfall and thus the supply of water in general means that it was not feasible to grow all of these crops in all of the regions occupied by Indus populations (Wright 2010, p. 168;Petrie 2017;Petrie et al 2017). Miller (2006Miller ( , 2015 has suggested that in central Punjab, water supply for Indus farmers is likely to have come primarily from inundation (produced by a combination of snowmelt and run-off from the Indian Summer Monsoon) and direct rainfall, while additional water was probably obtained via small-scale irrigation or well/lift irrigation. It is likely that these water supply mechanisms were used across the Indus zone, at differing levels of intensity, depending upon local environmental and climatic conditions (Petrie 2017).…”
Section: Differentiating Indus Cropping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterarchy in the Indus civilization co-existed with remarkable examples of coordination and standardization. In addition to Mohenjo-daro's street plans and drainage networks (Jansen 1993a), Indus agricultural production likely involved institutions that operated across kin or community boundaries (Miller 2015), and Indus craft industries coordinated activity among many different specialists (Bhan et al 1994;Kenoyer 1998;Menon 2008;Miller 2007a,b;Vidale 2000;Wright 1991;. A common system of stone weights has been recovered from many Indus sites, suggesting strong adherence to a single system (Miller 2013).…”
Section: Introductionmentioning
confidence: 99%